Effects of Additional Exercise Volume on Weight Loss, Oxidative Stress, and Inflammation in Young Wrestling Athletes - Kheirandish, Reza; Rahmani, Ahmad; Gorzi, Ali; Shaabani Ezdini, Ebrahim; Sadeghi , Atefeh (International Journal of Sport Studies for Health, 2024)
Background: Maintaining an optimal weight is essential for wrestlers, given their competition in weight-classified categories. However, many wrestlers resort to unhealthy methods of rapid weight loss, such as drastic caloric restriction and dehydration, which can adversely affect their overall wellbeing. Objective: This study aimed to examine the impact of a two-week increase in exercise volume on weight loss, serum oxidative stress, and inflammation in young wrestlers. Methods and Materials: Twenty wrestlers (aged 15-19, weight 63.47 kg) participated in a 2-week exercise intervention in addition to their regular weekly wrestling drills. The intervention consisted of resistance training, high-intensity interval training, and speed training. Wrestlers weighed daily over 2-week span. The participants’ superoxide dismutase (SOD), malondialdehyde (MDA), total antioxidant capacity (TAC), and serum interleukin-6 (IL-6) were measured both before and after the intervention. Data were analyzed using the paired t-test conducted through SPSS software, with a significant level set at p < 0.05. Results: The 2-week intervention resulted in significant weight loss (p<0.001). Within group comparisons found serum levels of IL-6, SOD, and TAC significantly increased from pre-to-post testing, but MDA did not change significantly. Conclusion: In conclusion, the present study demonstrates that a two-week increase in exercise volume can be an effective strategy for promoting weight loss and reducing oxidative stress in young wrestlers. The findings suggest that the improvement in antioxidant status is likely a result of the body’s response to increased inflammation, as indicated by changes in inflammatory markers.